THE EFFICACY OF DIFFERENT ORAL MAGNESIUM SUPPLEMENTS FOR MIGRAINE PREVENTION: A LITERATURE REVIEW - Alghadeer, Sultan (Indonesian Journal of Pharmacy, 2016)
No study was conducted to evaluate the efficacy of particular oral magnesium supplement over another in preventing migraine. Different magnesium supplements have different oral absorption and bioavailability. The objective was to identify the efficacy of different oral magnesium supplements in migraine prophylaxis. A literature review using MEDLINE, Scopus, Cochrane library, and EMBASE was conducted during the period from November 1, 2015 until December 30, 2015. Keywords included migraine, prophylaxis, and magnesium. Magnesium citrate was used as single oral migraine prophylactic supplement in most of the published trials. Migraine attack frequency and intensity were significantly lower in magnesium citrate group compared to placebo with 41.6-64% and 43-59% reduction in migraine attack frequency and severity frequently. Magnesium oxide was used in combination with magnesium citrate in 2 randomized clinical trials (RCTs), and used alone in one RCT in adults and children. No different in migraine frequency or severity between Mg-oxide and placebo in RCT conducted in children while Only Mg-oxide containing groups showed significant reduction in migraine days when compared to control (p<0.006) in RCT conducted in adults.Â  Magnesium chloride had never introduced as migraine prophylactic agent in clinical trials. Magnesium citrate seems to be the preferred oral magnesium supplement for migraine prevention; however, further studies comparing the efficacy of different oral magnesium supplements are needed.